Short-Term Gradation Loading Creep Properties and Failure Characteristics of High-Strength Fly Ash Concrete for Underground Engineering - Bing Li; Lianying Zhang; Hai Pu; Xianbiao Mao; Peitao Qiu; Zhong Zhao; Chao Ma (Advances in Civil Engineering)
In order to study the short-term creep deformation of high-strength concrete with varying fly ash replacement ratios, concrete samples with 0, 20, 35, and 50 wt% fly ash were tested using an electrohydraulic servocontrolled creep testing system and characterized using scanning electron microscopy after fracturing. Three different creep deformation behaviors were observed over time under different stress levels, namely, decelerating, isokinetic, and accelerating creep, where the creep rate increased with increasing stress. Failure of the samples occurred once isokinetic creep was achieved. The peak stress of the concrete samples exhibited a parabolic trend with increasing fly ash content, where the peak stress in the 0, 20, 35, and 50 wt% samples during short-term gradation loading creep testing was 13.08%, 7.94%, 15.14%, and 14.50% lower, respectively, than the peak stress measured in conventional uniaxial compression testing. The accumulated creep of the samples was reported and can be used as a reference for future studies on the long-term creep characteristics of concrete. The macro- and microscopic failure modes of the fly ash concrete during short-term gradation loading creep under uniaxial compression were brittle cleavage fracturing.